Revitalization of Islamic Values in The Character Building of Students Through Islamic Religious Education at SDN Ketapang 1 - Yudha Pratama, Muhammad (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2026)
In the era of globalization and digitalization, the main challenge faced by the world of education is the decline in the morals and character of students in elementary schools. This phenomenon shows the need to instill noble values as the foundation for building children's character. This study aims to describe the process of revitalizing Islamic values through Islamic Religious Education (PAI) and its influence on the character building of students at SDN Ketapang 1. The research approach used is qualitative with a case study, involving observation, in-depth interviews, and documentation techniques to obtain comprehensive data. The data were analyzed inductively through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of various methods, such as discussions, question and answer sessions, simulations, and stories about the Prophet and his companions, was able to increase the internalization of Islamic values and strengthen the affective and psychomotor aspects of students. The habit of routine religious activities, such as praying in congregation and reciting the Qur'an, also shapes students' spiritual discipline and positive character. Although there is a dependence on the lecture method, in general, this approach is able to create a pleasant learning atmosphere and has a positive effect on the character development of students. This study emphasizes the importance of strengthening values-based education as an effort to shape a young generation with Islamic character in the modern era